PENGARUH PEMANFAATAN SARI SELEDRI (APIUM GRAVEOLENS) TERHADAP PENYEMBUHAN KETOMBE KERING (PITYRIASIS CAPITIS) - lismawati, rts; Rostamailis, Rostamailis; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2013)
AbstractThis study aimed to analyze the of celery essence to cure the dry dandruff assessed from the level of skin itching, the amount dandruff, scalp conditionsansand hair loss levels. There were three treatments done they were: a control groupthat was controlled withont using the celery essence, an experimental group thatwas treated once day by using the celery essence, and the second experimentalgroup which was treated by using the celery essence once in two days. Thisresearch was an quasi experimental research. the Sampling was purposivesampling technique used by volunteers. The sampleÂ  9 student of UNP whoindicated suffering fromdry dandruff. The Data analysisÂ  was descriptive andanalytical Varian. Based on the reseach the results showed that the cure dandruffin the control group did not show a change towards the better on every indicator. More over, the effect of ising three differences treatment groups showedsignificantly resultson eachindicator. The use of celery juice could cure dandraffconsiderably with the appro prate frequency used eksperimenal group which wastreated. Keywords: Celery Juice, drydandruff.